On Mrs. Sommers’ Self-construction from the Perspective of Theory of Mirror Stages - Jiang, Yong (Journal for the Study of English Linguistics, 2023)
The short story A Pair of Silk Stockings depicted the protagonist Mrs. Somers’ process of finding her ideal self through a fifteen dollar consumption, reflecting the difficult situation of American women wandering between housewives and their ideal self in the 19th century. Mrs. Sommers’ self-exploration and alienation in the process of consumption, and her identity construction is quite in accordance with the three stages of one’s establishment in Jacques Lacan’s Theory of Mirror Stages.